FEATURES OF RUMOR MONGERING AND SLANDERING IN ISLAMIC HISTORY; IT'S FORMS AND EFFECTS IN MODERN ERA - Khubaib Usmani; Mahmood ul Hasan (Journal of Religion and Society, 2024)
This study explores the phenomenon of rumor-mongering and slandering within the context of Islamic history, highlighting its defining features and significant events that illustrate its destructive potential. In Islamic tradition, these acts are strongly condemned, as they undermine social harmony. The research delves into historical incidents, such as the infamous "Incident of Slander" (Hadith al-Ifk), to analyze how rumors and slander were addressed in early Islamic society and the measures prescribed in the Quran and Hadith to combat them. In the modern era, the advent of digital media and instant communication has amplified the scale and speed of rumor propagation. The study examines contemporary forms of rumor-mongering, including social media misinformation, political propaganda, and character assassination, along with their far-reaching impacts on individual reputations, community relationships, and global peace. By contrasting historical teachings with present-day realities, the paper emphasizes the timeless relevance of Islamic principles in addressing this pervasive issue and offers insights into ethical guidelines for curbing the spread of falsehoods in the digital age. Keywords: Rumor-Mongering, Slandering, Misinformation, Islamic Principles, Modern Era.